Migrating Texts Circulating Translations around the Eastern Mediterranean - Booth, Marilyn (Edinburgh University Press, 2019)
Explores translation in the context of the multi-lingual, multi-ethnic late-Ottoman Mediterranean world.Fénelon, Offenbach and the Iliad in Arabic, Robinson Crusoe in Turkish, the Bible in Greek-alphabet Turkish, excoriated French novels circulating through the Ottoman Empire in Greek, Arabic and Turkish: literary translation at the eastern end of the Mediterranean offered worldly vistas and new, hybrid genres to emerging literate audiences in the nineteenth and early-twentieth centuries. Whether to propagate 'national' language reform, circulate the Bible, help audiences understand European opera, argue for girls' education, institute pan-Islamic conversations, introduce political concepts, share the Persian Gulistan with Anglophone readers in Bengal, or provide racy fiction to schooled adolescents in Cairo and Istanbul, translation was an essential tool. But as these essays show, translators were inventors, and their efforts might yield surprising results.